Dual bases for noncommutative symmetric and quasi-symmetric functions via monoidal factorization. (July 2016) - Bui, V.C.; Duchamp, G.H.E.; Hoang Ngoc Minh, V.; Kane, L.; Tollu, C.
Abstract: We propose effective constructions of dual bases for the noncommutative symmetric and quasi-symmetric functions. To this end, we use an effective variation of Schützenberger's factorization adapted to the diagonal pairing between a graded space and its dual.